2019
DOI: 10.1056/nejmoa1910836
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Survival with Combined Nivolumab and Ipilimumab in Advanced Melanoma

Abstract: Terms of use This work is brought to you by the University of Southern Denmark through the SDU Research Portal. Unless otherwise specified it has been shared according to the terms for self-archiving. If no other license is stated, these terms apply: • You may download this work for personal use only. • You may not further distribute the material or use it for any profit-making activity or commercial gain • You may freely distribute the URL identifying this open access version T h e ne w e ngl a nd jou r na l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
2,452
11
62

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,886 publications
(2,772 citation statements)
references
References 15 publications
56
2,452
11
62
Order By: Relevance
“…3 Cumulative ipilimumab administration can induce the same disorder by inhibiting CTLA-4, resulting in regulatory T-cell (Treg) dysfunction. A clinical trial of NI combination therapy for metastatic melanoma showed no severe pancytopenia and hematological-related deaths, 4 but the ipilimumab dose in this trial (3 mg/kg) was lower than that (10 mg/kg) used in clinical trials that reported death due to pancytopenia or toxicity. 1,5 Although NI can cause CTLA-4 inhibition to induce Treg dysfunction that results in fatal pancytopenia, our…”
Section: Immune-related Pancytopenia Caused By Nivolumab and Ipilimumcontrasting
confidence: 58%
See 1 more Smart Citation
“…3 Cumulative ipilimumab administration can induce the same disorder by inhibiting CTLA-4, resulting in regulatory T-cell (Treg) dysfunction. A clinical trial of NI combination therapy for metastatic melanoma showed no severe pancytopenia and hematological-related deaths, 4 but the ipilimumab dose in this trial (3 mg/kg) was lower than that (10 mg/kg) used in clinical trials that reported death due to pancytopenia or toxicity. 1,5 Although NI can cause CTLA-4 inhibition to induce Treg dysfunction that results in fatal pancytopenia, our…”
Section: Immune-related Pancytopenia Caused By Nivolumab and Ipilimumcontrasting
confidence: 58%
“…To date, only one such case has been reported in the published work. 4 In that case, SCC occurred 20 years after the onset of PCC. The patient had a history of smoking and use of immunosuppressants, which are also considered as risk factors.…”
Section: Squamous Cell Carcinoma Arising From Plasma Cell Cheilitis Smentioning
confidence: 88%
“…Cardiac complications such as myocarditis are rare but can be fatal. In addition, neurologic complications must be taken seriously, as myasthenia gravis, peripheral neuropathy, and Guillain‐Barre have been reported …”
Section: Medical Oncology Perspective: Systemic Therapy Decision Makingmentioning
confidence: 99%
“…In the previous years novel target therapies and immunotherapies improved overall survival (OS) and progression free survival (PFS) rates (ranging from 37% to 55%) . However only a part of MM patients demonstrate to have benefits and patient selection has become imperative.…”
Section: Introductionmentioning
confidence: 99%